Effect of biomass Azolla microphylla on physical parameters of water quality in peat soil ponds - Parudan Bunga Ria Barutu; Syafriadiman Syafriadiman; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted on August - Sept 2018 in the Kualu Nenas Village, Tambang District, Kampar regency, Riau Province. Objective of study was to determine the effect of different biomass A. microphylla increasing physics parameters of water on peatsoil.The method used in this study is an experimental method using a Complete Random Design (CRD) with 1 factor, 4 treatments and 5 replications. The treatment used in this experiment are P0 (without biomass of Azolla michrophylla), P1 (biomass Azolla michrophylla 20 g/m2), P2 (biomass Azolla michrophylla 40 g/m2) and P3 ( biomass Azolla michrophylla 60 g/m2).The water quality parameters measured in this study are, turbidity, TSS and temperature.The results showed that biomass of Azolla microphylla had not significantly different effect on changes in physical parameters of water on peat soil ponds but for description analysis P3 different than P0,P1 and P2. The best results that can improve the physical parameters of peat water are found in the treatment of Azolla michrophylla 60 g / m2 (P3) by increasing the turbidity(12,50 NTU); TSS (150 mg/L) and temperature (26 – 29 0C). Keyword : Azolla michrophylla, Physics parameters, Peat soil